Anima Chatbot: A Media for New University Students to Get Idea for Speaking - Suciati; Azizah Maulina Erzad (Future Science, 2024)
This study aims to explain the implementation, the advantages, and the challenges of using chatbot applications for learning writing. It was a qualitative research method. For collecting the data, the writers used questionnaires, observation, and documentation techniques. The research participants were 35 students of the English Education Department of Institut Agama Islam Negeri Kudus, Indonesia. The documentation of their chat with Anima was observed. The results showed that (1) the implementation of Anima Chatbot in class was under the lecturer’s guidance; (2) the advantages of Anima are finding the idea for speaking, learning vocabulary and grammar; saving time, and increasing their activeness; (3) and the students’ challenges when they used Anima chatbot are the lack of vocabularies, grammar mastery, and the duration because the chatbot can response the chat so fast. The students are expected to be intensive to use Anima chatbot so that they can get more idea for supporting their spoken communication.